093: ASSOCIATION BETWEEN LEPTOSPIROSIS-RELATED KNOWLEDGE AND PRACTICES OF MALE PEDICAB DRIVERS IN SOME AREAS IN MANILA CITY. (24th August 2015) - Palatino, Maylin C; Lim, Patricia Abigail C; Reyes, Ma. Bituin S; Lim, Raphael Jourdain L; Vasquez, Diana Jean V
Abstract : Background: Leptospirosis is a pervasive disease that affects both animals and humans. 1 It is a potentially serious but treatable zoonotic disease, representing a worldwide public health hazard. 2 Poor sanitation and waste disposal coupled with rainfall and flooding can increase the incidence of leptospirosis in poor urban areas. 3 4 Although the trend of morbidity in the Philippines has steadily decreased over the past few years, 5 the disease still poses a major threat particularly in the urban areas that are prone to flooding.Because of the nature of occupation of pedicab drivers, they can be considered as part of the high-risk group. Objectives: The study aimed to determine if an association exists between leptospirosis-related knowledge and practices of pedicab drivers in Manila City. Methods: An analytic, cross-sectional study was done among 174 male pedicab drivers. Face-to-face interview was done using an interview schedule containing twelve questions on knowledge on transmission and prevention, and eight questions on their preventive occupation-related practices against leptospirosis. Logistic regression was employed to examine association while controlling for the confounding effect of other variables. Result: Forty-nine percent were found to have good knowledge on the transmission and prevention of leptospirosis while 21% had satisfactory preventive and health-seeking practice. After controlling for the confounding effect of pedicab ownership, the odds of having unsatisfactory practices among those with low knowledge was found to be thirteen times higher than those with good knowledge. Education was found to be an effect measure modifier. Conclusion: The result suggests that low education level combined with poor leptospirosis-related knowledge has a magnified effect on practices. Increasing the knowledge of pedicab drivers especially those with low education level is necessary to improve their practices. Information dissemination on leptospirosis should be further intensified. Collaboration between health workers and organizations of pedicab drivers can be done to organize health information seminars.